1996
DOI: 10.1086/647262
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Understaffing in Central Venous Catheter-Associated Bloodstream Infection

Abstract: Nursing staff reductions below a critical level, during a period of increased TPN use, may have contributed to the increase in CVC-BSI in the SICU by making adequate catheter care difficult. During healthcare reforms and hospital downsizing, the effect of staffing reductions on patient outcome (i.e., nosocomial infection) needs to be critically assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Seven research teams focused on BSI [1521], 1 team focused on urinary tract infection [22], and 1 team focused on ventilator-associated pneumonia [23]. The studies employed cross-sectional and cohort research designs, and the sample sizes ranged from 19 units to >13,000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Seven research teams focused on BSI [1521], 1 team focused on urinary tract infection [22], and 1 team focused on ventilator-associated pneumonia [23]. The studies employed cross-sectional and cohort research designs, and the sample sizes ranged from 19 units to >13,000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nursing staff reductions below a critical level may contribute to increase catheter-related infection by making adequate catheter care difficult. One study reported a four times greater risk of catheter infection when the patient-to-nurse ratio was doubled [14]. Moreover, replacement of regular nurses by float nurses further increases the risk of device-related infections [15].…”
Section: Staff Educational/quality Improvement Programmentioning
confidence: 99%
“…care teams have been associated with substantially lower rates of catheter related infections [56]. In accordance to this understaffing has also been identified as an independent risk factor [57]. …”
Section: Infections Of Intravascular Devicesmentioning
confidence: 99%